The roles of financial knowledge, motivation and self efficacy on the influence of financial education toward financial literacy - Thomas, Partono; Mulyono, Kemal Budi; Setiaji, Khasan (Dinamika Pendidikan, 2016)
Surveys and researches showed that there were many low finance literacy in various places. It happened also in The Economics Faculty, Semarang State University/ Universitas Negeri Semarang, there were from 16 of 40 students who had good financial behaviors. It was contradictive because they have taken accounting subject who should make them good in financial literacy. The research on financial literacy had the contradiction, especially the influence of financial education variable on financial literacy. Therefore; this study raised the mediating variables; the consumer knowledge variable and psychological factor variables (motivation, self efficacy). This study was analyzed structurally divided into two analyses; descriptive analysis and path inferential analysis. Â The results of descriptive analysis showed that studentsâ financial literacy and financial education were in enough categories; whereas, motivation and self-efficacy were in good condition, and studentsâ financial knowledge was in unfavorable category. The results of path analysis showed that the variable of financial education did not have any direct influence Â toward financial literacy, but it had indirect influence through motivation. Then, the variable of financial education also did not have any direct influence toward self-efficacy, and self-efficacy did influence toward financial literacy and financial knowledge did not have any influence toward financial literacy. Thus; the learning process on Finance should involve three aspects; cognitive, affective, and psychomotor; and it needs the development of learning model on Finance to involve studentsâ activeness in managing their financial activities.